Characteristics of the Concept of Patriotism in Education of Ideal Youth - Salimov Maruf Eshdavlat (Genius Journals, 2022)
In this article, when providing information on the education of young people, while focusing on specific aspects of human qualities associated with the concept of patriotism, the problem of youth in Uzbekistan becomes a priority in public policy, and the future, i.e. Uzbekistan has its own place and unique aspects among stable and developed countries. There have been attempts to explain that the issue of youth is of particular importance. In this regard, the loyalty of young people who want to serve in the internal affairs bodies and the profession of military officers justified the feeling of greatness of the country
Keywords: youth; perfect man; future generation; upbringing